Treatment of tinnitus with cyclobenzaprine: an open-label study - Vanneste, Sven; Figueiredo, Ricardo; De Ridder, Dirk (International journal of clinical pharmacology and therapeutics, 2012)
Tinnitus is defined as an intrinsic sound sensation that cannot be attributed to an external sound source. Currently there are no standardized drug therapies for the treatment of tinnitus. Based on the analogy between pain and tinnitus it is suggested that among all antidepressant families that have been used for tinnitus, particular interest should be paid to the tricyclic group of drugs as they have an analgesic effect. The aim of the present study was to investigate the effect of a tricyclic pharmacological agent, namely cyclobenzaprine for the relief of tinnitus complaints. 65 patients, who received the drug treatment, were compared to 30 patients on a waiting list, who received no treatment. Analysis shows that cyclobenzaprine offers some benefit to patients with tinnitus on both tinnitus intensity and tinnitus distress, while a waiting list control group does not demonstrate any improvement: 24% of the tinnitus patients showed a clear response to cyclobenzaprine with a reduction of 53% on tinnitus intensity and 25% had a clear response to cyclobenzaprine with a reduction of 55% on tinnitus distress. It was further demonstrated that particular subgroups, namely pure tone tinnitus patients and unilateral tinnitus patients, respond better to cyclobenzaprine. Our results indicate that cyclobenzaprine is a promising drug to treat tinnitus particularly in certain subgroups. As there is a good risk-benefit ratio and there are currently no well-established, specific treatments for tinnitus, cyclobenzaprine might be worthwhile to further investigate.